Globalización y educación - Herminio Núñez Villavicencio (Ciencia Ergo Sum)
The first part of this paper briefly examines the concept of globalization and its most palpable effects, especially economic ones. The second part summarizes the theoretical frameworks of some renowned thinkers in regards to globalization. Changes observed in globalization after September 11, 2001 are discussed, as well as its effect on the education system